2018
DOI: 10.1080/15548627.2018.1483807
|View full text |Cite
|
Sign up to set email alerts
|

Defective autophagy in osteoblasts induces endoplasmic reticulum stress and causes remarkable bone loss

Abstract: Macroautophagy/autophagy is a highly regulated process involved in the turnover of cytosolic components, however its pivotal role in maintenance of bone homeostasis remains elusive. In the present study, we investigated the direct role of ATG7 (autophagy related 7) during developmental and remodeling stages in vivo using osteoblast-specific Atg7 conditional knockout (cKO) mice. Atg7 cKO mice exhibited a reduced bone mass at both developmental and adult age. The trabecular bone volume of Atg7 cKO mice was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 57 publications
3
118
0
1
Order By: Relevance
“…15 A recent study has also reported that deficiency of autophagy (autophagy-related 7; ATG7) triggers ER stress to promote apoptosis and inhibit osteoblast mineralization and induce bone loss in which CHOP may regulate the activity of RUNX2 via separation from C/EBPb. 24 In the present study, we found the significant decrease in BMD and bone microstructure of tibias in Chop À/À mice and also detected the significant inhibition of osteoblastogenesis in BMSCs isolated from Chop À/À mice. These findings are consistent with the previous results.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…15 A recent study has also reported that deficiency of autophagy (autophagy-related 7; ATG7) triggers ER stress to promote apoptosis and inhibit osteoblast mineralization and induce bone loss in which CHOP may regulate the activity of RUNX2 via separation from C/EBPb. 24 In the present study, we found the significant decrease in BMD and bone microstructure of tibias in Chop À/À mice and also detected the significant inhibition of osteoblastogenesis in BMSCs isolated from Chop À/À mice. These findings are consistent with the previous results.…”
Section: Resultssupporting
confidence: 70%
“…Shirakawa et al have found that CHOP is a dominant‐negative inhibitor for C/EBPβ signaling and inhibits osteoblastogenesis, but induces osteoblast differentiation under the treatment of bone morphogenetic protein (BMP), suggesting that endogenous CHOP may play dual regulatory roles in osteoblastogenesis and bone formation . A recent study has also reported that deficiency of autophagy (autophagy‐related 7; ATG7) triggers ER stress to promote apoptosis and inhibit osteoblast mineralization and induce bone loss in which CHOP may regulate the activity of RUNX2 via separation from C/EBPβ . In the present study, we found the significant decrease in BMD and bone microstructure of tibias in Chop −/− mice and also detected the significant inhibition of osteoblastogenesis in BMSCs isolated from Chop −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al found that both deletion of the autophagy-related gene ATG7 and pharmacological inactivation of autophagy ameliorated bone loss in osteoporosis rats 29 . In contrast, Li et al suggested that defective autophagy in osteoblasts induces endoplasmic reticulum stress and causes osteoporosis 30 . However, the intracellular location of autophagy was not investigated in these studies.…”
Section: Discussionmentioning
confidence: 96%
“…‒ An early study using electron microscopy showed that autophagy increased in PDL cells located on the pressured side of orthodontic teeth during OTM . In addition, previous studies also found that autophagy had a profound effect on bone mineralization and homeostasis through the RANKL and OPG signaling pathway . Autophagy proteins were demonstrated to have essential roles in generating the osteoclast ruffled border and bone resorption .…”
Section: Introductionmentioning
confidence: 92%